Contiguous Governance of Synchronic and Diachronic Changes for the Use of Genome Editing Technologies - Minari, Jusaku; Shinomiya, Nariyoshi; Takashima, Kayo; Yoshizawa, Go (Frontiers in Political Science, 2022)
Genome editing technologies are increasingly coming under scrutiny, based on various social value judgments in biomedical research, clinical care, and public health. A central cause of this sociotechnical tension is that these technologies are capable of precisely and easily creating genome-modified organisms and human cells and tissues. To exemplify a general framework for a national governance system of genome editing technologies, we first look at the regulatory dynamics in Japan. Second, we expose the potential tension between national and international debates and directions for the global harmonization of genome editing technologies. Third, underpinning these two perspectives, we propose contiguous governance as a novel model of the governance of emerging biotechnologies from both synchronic and diachronic perspectives. These perspectives, derived from genome editing technologies, can contribute to a better understanding and consideration of future regulations and governance systems.